METHODOLOGY FOR USING INNOVATIVE TECHNOLOGIES WHEN TEACHING RUSSIAN TO FOREIGN STUDENTS (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation This article discusses some methods of using innovative technologies in the process of teaching Russian to foreign students. The relevance of innovative teaching lies in the use of person-centered learning, as well as in the search for conditions for unleashing the student’s creative potential, which is the main requirement of modern education.